Venous Thromboembolism and Route of Delivery - Review of the Literature - Evangelista,Matheus Schimidt (2018)
Abstract Venous thromboembolism events are important causes of maternal death during pregnancyandthepostpartumperiodworldwide.Are view of the literature with the objective of evaluating venous thromboembolism events in the puerperium according to the route of delivery was performed through a bibliographic survey in the Medline, LILACS and Scielo databases. We observed that patients submitted to cesarean sections present a significantlyhigher riskofdeveloping venousthromboembolismwhencomparedwiththose who undergo spontaneous vaginal delivery. The pathophysiological bases for this difference were explored and described in this review, as well as the indications of prophylaxis and treatment. Doctors and health professionals must be continuously vigilant regarding this condition, since it is associated with high morbidity and mortality.